Epistemological Peacebuilding in Mohammed Arkoun’s Dialogical Ethics: From Closed Reason to Open Reason - Tita Rostitawati; Taufik Ajuba; Ahmad Khoirul Fata (Sekolah Tinggi Agama Islam Sadra, 2026)
Religious conflict in plural societies is often addressed through value-based approaches that emphasize tolerance, harmony, and moderation. However, these approaches do not sufficiently explain the epistemological structures through which religious truth is produced, authorized, circulated, and defended. This research reconstructs an epistemological peacebuilding model from the perspective of an Islamic philosopher, namely Mohammed Arkoun, by examining how reasoning closed religious reasoning generates exclusion and how open reason can support dialogical peace. The study applies a qualitative critical-philosophical method with a historical-hermeneutic orientation to Arkoun’s major works, especially Critique of Islamic Reason, The Unthought in Contemporary Islamic Thought, and Rethinking Islam. The analysis focuses on la raison close, la raison ouverte, l’impensé, orthodoxy, and interpretive authority. The analysis shows that religious conflict becomes epistemological when interpretive authority is monopolized, inherited interpretations are treated as final truth, and alternative voices are excluded from legitimate discourse. Conversely, la raison ouverte enables peacebuilding by reopening religious reasoning to historical critique, epistemic humility, dialogical recognition, and ethical public reasoning. This article proposes an epistemological peacebuilding model comprising the diagnosis of closed reason, the deconstruction of absolute claims, and the dialogical construction through open reason. Peacebuilding should therefore be understood not merely as a moral appeal or a procedural conflict-resolution technique, but as a transformation of the epistemic conditions that shape religious truth, authority, and recognition in plural societies.